A Comparison of Adjusted Versus Unadjusted Doses of Polymyxin B Based on Renal Function and Incidence of Acute Kidney Injury. (June 2020) - Peyko, Vincent; Cohen, Henry
Purpose: To determine whether or not polymyxin B needs dose adjustments based on renal function by comparing the incidence of acute kidney injury (AKI) in patients whose polymyxin B doses were adjusted versus not adjusted according to renal function. Methods: This was a single-center, prospective study with a retrospective cohort taking place in an acute care community hospital. Forty-two patients treated with polymyxin B were evaluated between April 2012 and December 2015. The primary outcome was incidence of AKI at day 7 after initiation of polymyxin B therapy with secondary outcomes including microbiological cure, clinical cure, and 30-day mortality. Results: There was no difference in the incidence of AKI at day 7 in patients with polymyxin B doses adjusted according to renal function versus patients without polymyxin B dose adjustment (20.0% vs 18.2%; P = .882). There were no differences between groups in occurrence of microbiological cure, clinical cure, or 30-day mortality (27.8% vs 57.1%; P = .065, 70.0% vs 72.7%; P = .845, 40.0% vs 31.8%; P = .581, respectively). Conclusion: The results from this study support the use of polymyxin B without any dose adjustment in the setting of renal impairment.